STRATEGI PENGEMBANGAN PROFESIONALISME GURU BERBASIS KELEMBAGAAN DAN PERSONAL DI MTS NEGERI 1 MAGELANG - Atto Maulana; Rohmah Nur Azizah; Annisa Damayanti; Dias Ridho Pangestu (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
Teacher professional development is a crucial aspect in improving the quality of education, particularly in the era of globalization and rapid technological advancement. Teachers are required not only to master the subject matter, but also to adapt, innovate, and create meaningful learning experiences. This study aims to examine the strategies for developing teacher professionalism at MTs Negeri 1 Magelang through two main approaches, namely institutional and personal. This research employed a descriptive qualitative method with data collected through interviews and document studies. The data were analyzed inductively to identify patterns of strategies implemented by the school as well as teachers’ individual initiatives. The findings indicate that institutional strategies include annual training programs with professional resource persons, thematic workshops according to needs (such as the Merdeka Curriculum and digital media), informal consultation forums, and the creation of a collaborative and supportive school environment. Meanwhile, personal strategies are reflected in teachers’ participation in MGMP, involvement in external training, the adoption of interactive learning methods, the use of video-based digital media, and empathetic approaches such as home visits to better understand students’ backgrounds. The discussion emphasizes that teacher professional development is not only dependent on institutional support, but also highly influenced by teachers’ awareness and lifelong commitment to learning. Therefore, this study recommends several alternative strategies, including the establishment of pedagogical reading clubs, the implementation of peer review systems among teachers, and the integration of interactive e-learning platforms to strengthen both pedagogical and technological competencies. The synergy between institutional and personal strategies is essential for achieving sustainable professionalism, improving learning quality, and enhancing the readiness of madrasahs to face the challenges of globalization.